Moda-festa e cultura mineira no recorte territorial de Belo Horizonte - MG - Gabriela Carneiro Reis (2016)
This research aimed to determine whether aspects of Minas Gerais state (southeastern Brazil) culture are seized and expressed on fashionable party made in state capital: Belo Horizonte. For this analysis, performed from a humanistic and territorial approach and focusing on regional culture and fashion, has adopted as priority the creative process in the preparation of clothes in the context of "party fashion". From there, understanding culture as the sum of behaviors, knowledge, values and techniques whose territory becomes locus of this manifestation and also understanding fashion as a cultural expression, the process of creation was the starting point to identify if, indeed, there is an expression of the regional culture in Fashion